ANALYZING CHILDREN'S TREATMENT AND ROLE IN INDONESIAN RESEARCH: CURRENT PRACTICES AND ETHICAL CONSIDERATIONS - Sidik , Ezis Japar; Utomo, Dhafid Wahyu; Subandowo, Dedy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
This study investigates the treatment and role of children in research practices in Indonesia. Using a content analysis of six research-based articles, this study aims to understand the current state of involving children in research in Indonesia. The articles were selected based on three criteria: the focus of child research, the disciplines of research, and the availability of English language versions. The content analysis was carried out by systematically examining how each article addressed ethical considerations, participant involvement, and the research methodologies employed, particularly in relation to children as research participants. The findings show that researchers often fail to provide adequate treatment for child participants and tend to treat them similarly to adult participants throughout the research process. Additionally, children's involvement in research is not always voluntary, as evidenced by the lack of informed consent or consent from adult guardians, posing a risk to their safety and well-being. To address these issues, this study highlights the need for ethical guidelines that encompass specific aspects, such as obtaining genuine informed consent, safeguarding child welfare during research, and respecting children's unique vulnerabilities and rights. Existing frameworks like UNICEF's Ethical Research Involving Children (ERIC) guidelines or international research ethics codes could be adapted to the Indonesian context. Other relevant research institutions, such as the Ministry of Research, Technology and Higher Education, universities, and research communities, must also establish these guidelines to ensure ethical standards are upheld in research with children.